A Case Report of a Giant Pheochromocytoma - Lubis, Dian Anindita; Harahap, Agnes Stephanie; Em Yunir (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Pheochromocytoma is a rare catecholamine secreting tumor that are usually arise from adrenal medulla and produces signs and symptoms of excessive catecholamine secretion from tumor. A 32 years old female presented to the hospital, with dyspeptic symptoms. She had fluctuative hypertension, palpitation and sweating. Abdominal ultrasonography showed a right adrenal mass, and computed tomography of the adrenal glands confirmed a right adrenal mass. However, clinical biochemistry tests specific for pheochromocytoma was not performed. Laparoscopic right adrenalectomy was done and the adrenal tumor was excised. Histopathology and immunohistochemistry confirmed the diagnosis of adrenal pheochromocytoma; the tumor cells being positive for chromogranin, synaptophysin, S-100 protein, and inhibin. Following the surgery, the patient did well and showed full recovery at follow-up after 1 month.